Generación y aprovechamiento de nitrógeno bien expresado a partir de la asociación simbiótica azolla-anabaena en el cultivo de lechuga (Lactuca sativa L.) en la parroquia Vilcabamba, cantón y provincia de Loja - Calle Herrera, Yajahira Alexandra (2022)
Azolla filiculoides is a buoyant aquatic fern capable of fixing atmospheric nitrogen in symbiosis with anabaena bacteria and transforming it into assimilable forms for plants; in addition to this, during its development, it generates nitrogen in the biomass and in the water that, when it is incorporated into the soil, provides advantages, increasing fertility and soil structure. In order to contribute to peasant family agriculture, it was proposed to obtain and harness well-expressed nitrogen from the azolla-anabaena symbiosis in conditions accessible to farmers in the lettuce crop. The investigation was carried out in the Vilcabamba parish; in a completely randomized design, with three repetitions; five treatments were tested: testigo, NitrAgua, Urea, Azolla y Azolla plus NitrAgua; data on plant height, number of leaves, stem diameter and weight at 15, 30 and 60 days were collected. The best results were obtained after 60 days with the input of Azolla and NitrAgua biomass: 20 cm plant height, 2 cm stem diameter, 18 leaves per plant and 114 g weight. The joint application of Azolla biomass as a substrate plus irrigation with NitrAgua is an effective biofertilizer since the lettuce crop benefits from a well-expressed nitrogen contribution. The characteristics of the water in the azollario were: pH 7.5, average environmental temperature of 22°C, nitrogen content in the azollario maximum of 130 mg/l. Key words: Biofertilizer, Fixation the Nitrogen, Azolla, NitrAgua.